Phenotypic analysis of mast cell granule proteinases in normal rat bone marrow cultures. - McMenamin, C (1987)
Mast cells with morphological and some biochemical properties of mucosal mast cells (MMC) proliferate and mature in rat bone marrow cultures stimulated with factors from antigen- or mitogen-activated T lymphocytes. There has been much controversy over the criteria used to distinguish the different mast cell subsets, and because histochemistry of granule glycosaminoglycans does not adequately define mast cell subsets morphologically, the proteinase phenotypes of cultured mast cells were analysed. Affinity-purified cross-absorbed monospecific F(ab')2 antibodies raised against rat mast cell protease I (RMCPI) from connective tissue mast cells (CTMC) and against rat mast cell protease II (RMCPII) isolated from mucosal mast cells were used to stain granule proteinase by an immunohistochemical technique. Mast cells grown in culture from normal rat bone marrow stained exclusively with anti-RMCPII antibodies, thus providing further confirmation of their similarity to, and identity with, MMC.